Pembuatan Aplikasi Crowdsource Untuk Jasa Rumah Tangga Berbasis Android - Kristofer Danela Lukito; Liliana Liliana; Henry Novianus Palit (Jurnal Infra, 2017)
The search process for domestic services have tended to be difficult because of the lack of centralized information media. The process of offering services performed by service providers is also difficult because of the absence of promotional media that can be accessed by service customers. Based on these requirements, crowdsource application was made for the services of domestic workers that can be a source of information as well as to help connecting service customers with service providers. Crowdsource application for the services of domestic workers is designed into a Service Provider Application, a Service Customer Application, and a Registration and Administrator Website. Registration Website is used to allow users to enroll as a provider. The website also serves for the administrator to accept or reject registration and to activate or deactivate an account. Service Provider Application and Service Customer Application function to communicate with each other in order to reach an agreement of supply and demand services. The results show that the Service Provider Application and Service Customer Application can provide the necessary information and help users communicate, negotiate, and reach an agreement. Review and report violations feature helps to evaluate every element in the application, both service providers, service customers, demand, and supply.